2018
DOI: 10.7287/peerj.preprints.26768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering the hidden players in Lepidoptera biology: the heritable microbial endosymbionts

Abstract: The Lepidoptera is one of the most widespread and recognisable insect orders. Due to their remarkable diversity, economic and ecological importance, moths and butterflies have been studied extensively over the last 200 years. More recently, the relationship between Lepidoptera and their heritable microbial endosymbionts has received increasing attention. Heritable endosymbionts reside within the host’s body and are often, but not exclusively, inherited through the female line. Advancements in molecular genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 161 publications
1
20
0
Order By: Relevance
“…44 Moreover, the existence of endosymbionts indicates strict vertical transmission of certain bacteria within host lineages. 46 Despite the strong taxonomic variability, we found that the metabolic potential of gut prokaryotic communities, in terms of the relative abundances of proxy genes, was similar among caterpillars and was possibly dependent on body size. Currently, there are only three shotgun sequencing-based gut metagenomes for Lepidopteran insects.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…44 Moreover, the existence of endosymbionts indicates strict vertical transmission of certain bacteria within host lineages. 46 Despite the strong taxonomic variability, we found that the metabolic potential of gut prokaryotic communities, in terms of the relative abundances of proxy genes, was similar among caterpillars and was possibly dependent on body size. Currently, there are only three shotgun sequencing-based gut metagenomes for Lepidopteran insects.…”
Section: Discussionmentioning
confidence: 65%
“…Species differences in host physiology and local gut environment, such as pH, oxygen levels and redox conditions, can contribute to variation in microbiotas . Moreover, the existence of endosymbionts indicates strict vertical transmission of certain bacteria within host lineages …”
Section: Discussionmentioning
confidence: 99%
“…As recently reported, only 16.3% of the Lepidopteran caterpillars are infected by Wolbachia with different impacts of the endosymbiotic bacteria on the reproduction and the sex ratio of their host e.g. male killing, feminization and cytoplasmic incompatibility (Duplouy and Hornett, ).…”
Section: Discussionmentioning
confidence: 96%
“…As recently reported only 16.3% of the Lepidopteran 333 caterpillars are infected by Wolbachia with different impacts of the endosymbiotic bacteria 334on the reproduction and the sex ratio of their host e.g. male killing, feminization, and 335 cytoplasmic incompatibility(Duplouy and Hornett, 2018). 336 337Effects of host plant's microbiota and metabolite composition 338The microbiome of plant phyllosphere is partially conserved across species with presence 339 of recurrent taxa such as Methylobacterium, Pseudomonas and Sphyngobium(Delmotte et 340 al., 2009).…”
mentioning
confidence: 99%